Islamic Proscribed Transactions' Terms In Prophetic Hadith: A Semantic Linguistic Study/ مصطلحات المعاملات المحظورة في الإسلام في الأحاديث النبوية: دراسة لغوية دلالية - Omar Md Din; Abdul Ghani Bin Md Din; Sami Samir Abdelfattah; Ibrahim Wanni Tohyala (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study conducts a philological and juridical analysis of selected terminology in Prophetic Hadiths concerning al-buyūʿ al-manhiyy ʿanhā (Islamic proscribed transactions). It delineates their etymological foundations and subsequent semantic transmutation into sharʿī (juridical) connotations as contextualized within the Hadith corpus, analyzing the relationship between linguistic and the jurisprudential sharʿī and their points of interconnection. The study interrogates hermeneutic divergences among lexicographers and fuqahāʾ (Islamic jurists) concerning the semantic boundaries of these terms, reconciling multiple interpretations where possible and prioritizing the most plausible ones when reconciliation is unattainable. The methodology critically engages classical lughawī (linguistic) commentaries, Sharh al-ḥadīth (Hadith exegeses), and gharīb al-ḥadīth (lexical studies of rare Hadith terminology) to triangulate semantic inferences. Additionally, the study traces the semantic development of these terms or phrases from their linguistic roots to their jurisprudential applications. The research adopts a descriptive-analytical methodology to study and dissect these terms. Key findings include: Linking linguistic and jurisprudential meanings is essential for uncovering a term’s true signification, and Surveying and compiling scholarly opinions can yield decisive insights into a term’s meaning